2019
DOI: 10.21037/atm.2019.07.91
|View full text |Cite
|
Sign up to set email alerts
|

Concise update on colorectal cancer epidemiology

Abstract: Colorectal cancer is a type of gastrointestinal malignancy originating from either the colon or rectum. In this short report we provide a concise update on recent colorectal cancer statistics, especially concerning frequency, mortality, life expectancy and risk factors. Overall, colorectal cancer is the third more frequent malignant disease around the world (1.85 million of new cases/years; 10.2% of total malignancies), with 2.27% cumulative risk of onset between 0-74 years. The age-standardized rate increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
181
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(185 citation statements)
references
References 13 publications
1
181
0
3
Order By: Relevance
“…24 Of note, both colorectal cancer and prostate cancer have a significant better 5-year overall survival of 64% and 88%, respectively, underscoring the significance of our findings in pancreatic cancer with a 5-year survival of barely 8%. 29,30 Strikingly, in this study we also demonstrated that IL-15 potentiates CD40 agonist treatment, causing an 8fold dose reduction in one of the PDAC mouse models which has not been reported so far. This important dose reduction could be of great translational importance as lower doses might significantly decrease adverse events in patients.…”
Section: Discussionsupporting
confidence: 60%
“…24 Of note, both colorectal cancer and prostate cancer have a significant better 5-year overall survival of 64% and 88%, respectively, underscoring the significance of our findings in pancreatic cancer with a 5-year survival of barely 8%. 29,30 Strikingly, in this study we also demonstrated that IL-15 potentiates CD40 agonist treatment, causing an 8fold dose reduction in one of the PDAC mouse models which has not been reported so far. This important dose reduction could be of great translational importance as lower doses might significantly decrease adverse events in patients.…”
Section: Discussionsupporting
confidence: 60%
“…Total number of samples of the gene (1) For every gene in the CRC pathway, we computed this probability separately for healthy and tumor samples from the GSE44076 dataset and evaluated the ratio. We define the ratio of probabilities (ROP) as, ROP = P Gene is over-expressed in tumor samples P Gene is over-expressed in healthy samples (2) Clearly, a ratio greater than 1 (i.e. ROP > 1) suggests that a particular gene is operating in an aberrantly up-regulated fashion in the tumor samples as compared to the healthy samples.…”
Section: Number Of Over-expressed Samples Of the Genementioning
confidence: 99%
“…[ 1 ] Although the 5-year relative survival rate was above 90% for patients with localized stage colorectal cancer, only about 14% for patients with distant tumor spread. [ 2 ] Therefore, early detection of CRC and understanding the molecular mechanism of distant metastases are urgently required. Several studies indicates detection of serum exosomes may be considered a non-invasive diagnosis of cancer and contribute to clarify the potential mechanisms for distant metastasis.…”
Section: Introductionmentioning
confidence: 99%